Extracellular vesicle-mediated regulation of macrophage polarization in bacterial infections - Qu, Mingjuan; Zhu, Hongwei; Zhang, Xingxiao (Frontiers in Microbiology, 2022)
Extracellular vesicles (EVs) are nanoscale membrane-enveloped vesicles secreted by prokaryotic and eukaryotic cells, which are commonly defined as Membrane Vesicles (MVs) and exosomes respectively. They play critical roles in the bacteria-bacteria and bacteria-host interactions. In infectious diseases caused by bacteria, as the first line of defense against pathogens, the macrophage polarization mode commonly determines the success or failure of the host’s response to pathogen aggression. M1-type macrophages secrete pro-inflammatory factors that support microbicidal activity, while alternative M2-type macrophages secrete anti-inflammatory factors that perform an antimicrobial immune response but partially allow pathogens to replicate and survive intracellularly. Membrane Vesicles (MVs) released from bacteria as a distinctive secretion system can carry various components, including bacterial effectors, nucleic acids or lipids to modulate macrophage polarization in host-pathogen interaction. Similar to MVs, bacteria-infected macrophages can secrete exosomes containing a variety of components to manipulate the phenotypic polarization of “bystander” macrophages nearby or long distance to differentiate into type M1 or M2 to regulate the course of inflammation. Exosomes can also repair tissue damage associated with the infection by up-regulating the levels of anti-inflammatory factors, down-regulating the pro-inflammatory factors, and regulating cellular biological behaviors. The study of the mechanisms by which EVs modulate macrophage polarization have opened new frontiers in delineating the molecular machinery involved in bacterial pathogenesis and challenges in providing new strategies for diagnosis and therapy.